Establishment and evaluation of a nomogram for in-hospital new-onset atrial fibrillation after percutaneous coronary intervention for acute myocardial infarction - Tu, Junjie; Ye, Ziheng; Cao, Yuren; Xu, Mingming; Wang, Shen (Frontiers in Cardiovascular Medicine, 2024)
Background: New-onset atrial fibrillation (NOAF) is prognostic in acute myocardial infarction (AMI). The timely identification of high-risk patients is essential for clinicians to improve patient prognosis. Methods: A total of 333 AMI patients were collected who underwent percutaneous coronary intervention(PCI) at Zhejiang Provincial People's Hospital between October 2019 to October 2020. Least absolute shrinkage and selection operator regression(Lasso) and multivariate logistic regression analysis were applied to pick out independent risk factors. Secondly, the variables identified were utilized to establish a predicted model and then internally validated by 10-fold crossvalidation. The discrimination, calibration, and clinical usefulness of the prediction model were evaluated using the receiver operating characteristic(ROC) curve, calibration curve, Hosmer-Lemeshow test decision curve analyses, and clinical impact curve. Result: Overall, 47 patients (14.1%) developed NOAF. Four variables, including left atrial dimension, body mass index(BMI), CHA2DS2-VASc score, and prognostic nutritional index, were selected to construct a nomogram. Its area under the curve is 0.829, and internal validation by 10fold cross-folding indicated a mean area under the curve is 0.818. The model demonstrated good calibration according to the Hosmer-Lemeshow test (P=0.199) and the calibration curve. It showed satisfactory clinical practicability in the decision curve analyses and clinical impact curve.This study established a simple and efficient nomogram prediction model to assess the risk of NOAF in patients with AMI who underwent PCI. This model could assist clinicians in promptly identifying high-risk patients and making better clinical decisions based on risk stratification.